Analisis Tata Kelola Sanitasi Lingkungan Pasar Rakyat Menuju Pasar Sehat Era New Normal Di Kota Yogyakarta - Morrin Choirunnisa Thohira; Faisol Rahman (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
A healthy market is a clean, safe, comfortable, and healthy market condition through the fulfillment of environmental quality standards, health requirements, as well as supporting facilities and infrastructure with the independence of the market community. Markets that have poor environmental sanitation management will have an impact on public health, especially when the new normal is enacted. This study aims to analyze the environmental sanitation management of the market in the new normal at the market in the city of Yogyakarta based on the Minister of Health Regulation No. 17 of 2020 concerning healthy markets and the Decree of the Minister of Health through KMK No. HK.01.07-MENKES-382-2020 concerning Public Health Protocols in Public Places and Facilities in the Context of Preventing COVID-19. This research is a descriptive observational study by placing the sample in the study using stratified random sampling, which is selected based on the qualifications of the market class I to class V located in the city of Yogyakarta and under the supervision of the Yogyakarta City Trade Office. Class I is represented by Beringharjo Market (eastern), class II Giwangan Market, class III Demangan Market, class IV Pasar Legi Patangpuluhan and class V Pasar Gedong Kuning. The results obtained are three markets that are categorized as healthy markets in a relaxed manner in the new normal era, namely East Bringharjo Market, Legi Patangpuluhan Market, and Gedong Kuning Market.